2017
DOI: 10.1590/0074-02760160549
|View full text |Cite
|
Sign up to set email alerts
|

ELISA-based assay of immunoglobulin G antibodies against mammalian cell entry 1A (Mce1A) protein: a novel diagnostic approach for leprosy

Abstract: BACKGROUNDLeprosy is a chronic infectious disease caused by the obligate intracellular bacillus Mycobacterium leprae. Because leprosy diagnosis is complex and requires professional expertise, new tools and methodologies are needed to detect cases in early stages and prevent transmission. The M. leprae genome contains mce1A, which encodes a putative mammalian cell entry protein (Mce1A). We hypothesised that the presence of Mce1A on the cell surface could be detected by the host's immune system.OBJECTIVEThe aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…[50][51][52] Mce1A-specific antibodies have been detected in leprosy patients, especially IgG antibodies were significantly higher in both MB and PB patients compared to controls. 53 This is in contrast to the general assumption that antibodies are predominant in the MB side of the leprosy spectrum only, and Mce1A-specific antibodies therefore show potential for the identification of PB patients as well. The four cell types that can internalize M leprae via Mce1A will be discussed next.…”
Section: Fir S T En Counter : S K In or Na Sal Epitheli Um?mentioning
confidence: 89%
See 1 more Smart Citation
“…[50][51][52] Mce1A-specific antibodies have been detected in leprosy patients, especially IgG antibodies were significantly higher in both MB and PB patients compared to controls. 53 This is in contrast to the general assumption that antibodies are predominant in the MB side of the leprosy spectrum only, and Mce1A-specific antibodies therefore show potential for the identification of PB patients as well. The four cell types that can internalize M leprae via Mce1A will be discussed next.…”
Section: Fir S T En Counter : S K In or Na Sal Epitheli Um?mentioning
confidence: 89%
“…These four cell types are most likely the first line of defense against M leprae, and tropism for these cells is potentially mediated via mammalian cell entry protein 1A (Mce1A) 50‐52 . Mce1A‐specific antibodies have been detected in leprosy patients, especially IgG antibodies were significantly higher in both MB and PB patients compared to controls 53 . This is in contrast to the general assumption that antibodies are predominant in the MB side of the leprosy spectrum only, and Mce1A‐specific antibodies therefore show potential for the identification of PB patients as well.…”
Section: First Encounter: Skin or Nasal Epithelium?mentioning
confidence: 99%
“…Quantitative assessment of IgA, IgM and IgG antibodies against the Mce1A protein was performed by indirect ELISA ( 15 ). Purified recombinant Mce1A protein was provided by Dr. LW Riley (University of California, Berkeley, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…The mammalian cell-entry 1A (Mce1A) protein, first described in M. tuberculosis , is present in the cell wall of M. leprae and it is associated with the entry of the bacillus into nasal epithelial cells and skin cells ( 13 , 14 ). Previous studies have shown the potential of using serum biomarkers such as antibodies against Mce1A in the diagnosis of HD ( 15 ). Therefore, because it plays a role in the invasion and maintenance of M. leprae infection, Mce1A represents a potential target for the development of new diagnostic tests to diagnose HD, monitor treatment, and screen for contacts of index cases of HD.…”
Section: Introductionmentioning
confidence: 99%
“…The immunoreactivity of anti-rMLP15 IgG in patient sera was assessed using a modified ELISA protocol of Lima et al (2017). In polystyrene 96-well ELISA plates (Kasvi™), 1 µg/well of rMLP15 in 100 μL of 0.1 M sodium carbonate buffer (pH 9.6) was coated and incubated for 16–18 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%